2016
DOI: 10.1111/ahg.12144
|View full text |Cite
|
Sign up to set email alerts
|

On Efficient and Accurate Calculation of Significance P‐Values for Sequence Kernel Association Testing of Variant Set

Abstract: Summary The objective of this paper is to discuss and develop alternative computational methods to accurately and efficiently calculate significance p-values for the commonly used sequence kernel association test (SKAT) and adaptive sum of SKAT and burden test (SKAT-O) for variant set association. We show that the existing software can lead to either conservative or inflated type I errors. We develop alternative and efficient computational algorithms that quickly compute the SKAT p-value and have well-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…It can be shown that under the null hypothesis, the above statistic in asymptotically follows a linear combination of chi‐square distributions (Chen, Han et al., ), 0trueSKATk=1mλW,kχk,12,where χk,12 is independently and identically distributed chi‐square distribution with degree of freedom ( df ) 1. Therefore, the P ‐value for SKAT can be estimated by the Davis’ approach or other methods (Davies, ; Wu, Guan, & Pankow, ). From , we know that the performance of SKAT depends on the weight matrix W .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that under the null hypothesis, the above statistic in asymptotically follows a linear combination of chi‐square distributions (Chen, Han et al., ), 0trueSKATk=1mλW,kχk,12,where χk,12 is independently and identically distributed chi‐square distribution with degree of freedom ( df ) 1. Therefore, the P ‐value for SKAT can be estimated by the Davis’ approach or other methods (Davies, ; Wu, Guan, & Pankow, ). From , we know that the performance of SKAT depends on the weight matrix W .…”
Section: Methodsmentioning
confidence: 99%
“…where 2 ,1 is independently and identically distributed chisquare distribution with degree of freedom (df) 1. Therefore, the P-value for SKAT can be estimated by the Davis' approach or other methods (Davies, 1980;Wu, Guan, & Pankow, 2016). From (3), we know that the performance of SKAT depends on the weight matrix .…”
Section: Notations and Skatmentioning
confidence: 99%
“…This entails computing the first two moments of Q under the null hypothesis and using these moments to estimate the degrees of freedom and a factor to rescale the χ 2 distribution. Liu et al () and Kwee et al () both applied the same Satterthwaite approximation, although this can be anticonservative at the extreme tail and higher moment‐matching methods have been proposed to improve accuracy (B. Wu & Pankow, ; B. Wu, Guan, & Pankow, ). For the sequence kernel association test (SKAT), M. C. Wu et al () considered a more accurate asymptotic approximation of the distribution of Q , recognizing that its distribution is a linear combination of i.i.d.…”
Section: Hypothesis Testing and P‐valuesmentioning
confidence: 99%
“…A challenge is computing reliable P ‐values for SKAT‐O when evaluating a range of values for the parameter ρ. It has been shown that the SKAT‐O P ‐values are less reliable than the SKAT P ‐values, and the performance of current SKAT‐O implementations depends on the set size of genetic markers and their correlation (B. Wu et al, ).…”
Section: Kernel Designs and Multiple Kernelsmentioning
confidence: 99%
See 1 more Smart Citation